COMPARATIVE EFFICACY OF Y-U ANTRAL ADVANCEMENT FLAP PYLOROPLASTY AND INVERTED PYLORUS DUODENAL PLASTY AS A RELIEF TO PYLORIC STENOSIS IN DOGS - M. Imtiaz; M. A. Khan; M. S. Khan; M. T. Sajjad; M. Ijaz; M. M. Ali; M. Imran (Journal of Animal and Plant Sciences, 2012)
Two established surgical techniques, Y-U antral advancement flap pyloroplasty and inverted pylorus duodenal plasty are used to treat the pyloric stenosis in dogs. The study was conducted on twelve healthy dogs of same age and body weight. The dogs were divided into three groups i.e. Group A, B and C comprising four animals each. The dogs in group A and B were subjected to Y-U antral advancement flap pyloroplasty and inverted pylorus duodenal plasty, respectively whereas the dogs in group C were kept as control. The evaluation of the procedures was done on the basis of clinical observation, gastric emptying time, contrast radiography and post euthanasia assessment. It was statistically proved that Gastric emptying time of group “B” was lesser than group “A”.  The efficacy of inverted pylorus duodenal plasty was better than Y-U antral advancement flap pyloroplasty in terms of convenience, short duration of operation, less post-operative complications, increased luminal diameter and better gastric drainage in short period of time.
Keywords: Pylorus; stenosis duodenalplasty; pyloroplasty; dog.